The effects of information flow, seniority and status on communication satisfaction within a United States federal bureaucracy. - Perez, Michael Andrew. (My University, 2000)
The effects of information flow on communication satisfaction within a federal bureaucracy were investigated. Specifically, this study investigated the effects of receiving quality information, feedback, and timeliness of information as well as the bureaucratic variables of age, grade, time in federal service and time in grade on communication satisfaction within a United States federal bureaucracy. This study used the Questionnaire Survey of the International Communication Association and the Perez Communication Survey for Federal Bureaucracies (PCSFB), validated in a pilot project survey of all federal employees of the Library System within U.S. Army, Europe (USAREUR). The full study was conducted through a survey of federal employees of the Army Continuing Education System within USAREUR. Analysis of survey data revealed statistically significant and positive relationships between communication satisfaction and the independent variables of receiving quality information, timeliness of information and feedback. The implications of these results permit researchers to conclude that receiving quality information, the timeliness of information received by organizational members and the feedback members provide have significant, positive effects on communication satisfaction within organizations.
Keywords: Speech Communication.; Communication in public administration United States.; Communication in public administration.; Political Science, Public Administration.; United States. Army. Europe and Seventh Army. Library Program.